Differential operators on manifolds - Vesenttni,E.; SpringerLink(Online service). (Berlin London, 2011)
Lectures:M.F.Atiyah:Classical groups and classical differential operators on manifolds.R. Bott:Some aspects of invariant theory in differential geometry.E.M.Stein:Singular integral operators and nilpotent groups.Seminars:P.Malliavin:Diffusion et geometrie differentielle globale.S.Helgason:Solvability of invariant differential operators on homonogeneous manifolds.
Electronic reproduction.
Keywords: Differential operators--Congresses.; Manifolds (Mathematics)--Congresses.